6th EuroCC Vilnius workshop on using HPC - Macernis, Mindaugas; Chmeliov, Jevgenij (Vilnius University Proceedings, 2026)
This one-day event covered various research topics utilizing High-Performance Computing (HPC) resources, including the Vilnius University supercomputer ‘VU HPC’ Saulėtekis at the Faculty of Physics and EuroHPC facilities. The topics ranged from quantum chemistry and molecular dynamics to experimental data relevant to the computational field, alongside discussions on potential academia–industry collaborations.
Keywords: -